Promotion in Increasing Sales Product Popularity: Study on Youth Perspectives - Paule Mbembae (Journal La Bisecoman, 2020)
Success or failure of a company that operates is always faced with costs, costs needed by the company. The use of social media can minimize promotion costs. Small and medium-sized businesses must begin to understand social media marketing so that products sold can sell quickly. A problem that is often faced by small and medium business people is the limited capital to advertise. Through social media marketing, small and medium businesses will save the cost of promoting their products. Modern marketing requires more than developing good products, setting competitive prices and making it easy for customers to reach. The younger generation will be very happy if business people know what they want automatically. In addition, they will also be open to a product if they are involved not as consumers but become friends. The advantage is that customers can easily submit responses or comments through social media, be it praise, criticism, or even suggestions.